(untitled) (Bangladesh Journal of Plant Taxonomy, 2025)
The present paper deals with seven seaweeds taxa namely, Blidingia minima (Kützing) Kylin, Bryopsis pennata Lamouroux and Halimeda simulans Howe from Chlorophyceae; Dictyopteris plagiogramma (Montagne) Vickers and Padina perindusiata Thivy from Phaeophyceae and Galaxaura obtusata (Ellis & Solander) Lamouroux and Liagora valida Harvey from Rhodophyceae have been identified, described, and illustrated as new records for Bangladesh. Of these, Blidingia is also a new generic record for Bangladesh. Bangladesh J. Plant Taxon. 32(1): 77-82, 2025 (June)